Design And Verification Of An Oscillating Wear Tester To Stimulate The Piston-Cylinder Tribology In Internal Combustion Engines - Al-Tmeemi, Bhaa Alden Hussein Ali (2011)
An Oscillating Wear Tester (OWT) was built to simulate the piston-cylinder tribology in internal combustion engines. This tester consists of load system, motion system and frictional force measurement system. It operates at a speed of 10-1500 rpm. AL 380-0-F die casting alloy used as blank (cylinder) and stainless steel specimen slider was fabricated as a ring in piston ring assembly. Simulation for the spring strain plate, blank and base assembly was conducted to find the stress and deformation by using SolidWorks,